Efficacy of depth jumps to elicit a post-activation performance enhancement in junior endurance runners - Blagrove, R. C.; Holding, K. M.; Patterson, S. D.; Howatson, G.; Hayes, P. R. (Journal of Science and Medicine in Sport, 2019)
Objectives: To determine the effect of performing depth jumps (DJ) pre-exercise on running economy (RE) and time to exhaustion (TTE) at the speed associated with maximal oxygen uptake (sVO2max) in a group of high-performing junior middle-distance runners. Design: Randomized crossover study. Methods: Seventeen national- and international-standard male distance runners (17.6 ± 1.2 years, 63.4 ± 6.3 kg, 1.76 ± 0.06 m, 70.7 ± 5.2 mL kg-1 min-1) completed two trials. Following a 5 min warm-up at 60% VO2max, participants performed a 5 min run at 20% <| below oxygen uptake corresponding with lactate turn-point to determine pre-intervention RE. Participants then completed either six DJ from a box equivalent to their best counter-movement jump (CMJ) or a control condition (C) involving body weight quarter squats. After a 10 min passive recovery, another 5 min sub-maximal run was performed followed by a run to exhaustion at sVO2max. Results: Compared to the C trial, DJ produced moderate improvements (-3.7%, 95% confidence interval for effect size: 0.25-1.09) in RE, which within the context of minimal detectable change is considered possibly beneficial. Differences in TTE and other physiological variables were most likely trivial (ES: <0.2). Individual responses were small, however a partial correlation revealed a moderate relationship (r = -0.55, p = 0.028) between change in RE and CMJ height. Conclusions: The inclusion of a set of six DJ in the warm-up routine of a well-trained young male middle-distance runner is likely to provide a moderate improvement in RE. ABSTRACT FROM AUTHOR